Pejibaye (Peach Palm) Growing in the Florida Home Landscape - Jonathan H. Crane (EDIS)
HS-1072, a 7-page fact sheet by Jonathan H. Crane, provides homeowners with a basic reference for growing pejibaye (peach palm) in the home landscape. Tables include suggested cultural practices by month and nutritional values. Published by the UF Department of Horticultural Sciences, February 2006.